Por mi alma subiré a Dios. El concepto de alma de san Agustín de Hipona. (2013)
This article seeks to establish the key elements of the doctrine of the soul of St. Augustine of Hippo. Magna natura et magna quaestio est (De Hippo; trans.; 1968; 14; 4; 6); since it will take lifetime thought and works of the holy bishop. Searching your own soul; deep into its sanctuary; discovering the image of God in it; his goodness; his greatness; his life ... to put it back to God; its origin and goal of all its efforts. This is the path the Thagaste philosopher shows us; thirsty of truth; that will eventually be dumped into the source that satiates the same Truth.